الأسس الخاصة لتولي الموظف العام مهام الوظيفه العامه - علاونة, فادي (University of Eloued جامعة الوادي, 2022)
الأسس الخاصة لتولي الموظف العام مهام الوظيفه العامه The special foundations for the general employee to assume the duties of his job الملخص تناول هذا البحث والذي موضوعه الأسس الخاصة لتولي الموظف العام مهام الوظيفه العامة جميع الاحكام والقواعد الأساسية التي تتيح للموظف تولي مهام الوظيفه العامة بدءاً من شروط التعيين والتي تم الحديث عنها في المطلب الأول سواء كانت شروط خاصة بالوظيفه أم شروط خاصة بالموظف ذاته ، إضافة الى أهم المبادئ التي تحكم التعيين في الوظيفه العامه ، وهذا جميعه ضمن بند الضوابط التي تحكم الوظيفه العامه ، في حين تم الحديث في المطلب الثاني عن طرق إختيار الموظفي وإرتباطهم بالوظيفه العامه ، وقد تم الحديث عن طرق التكليف ، والانتخاب ، واسلوب المقابلة والامتحان الكتابي والشفاهي ، وأسلوب العقد بصفتها الوسائل التي تخلق العلاقة التنظيمية للموظف مع الإدارة . وقد توصل البحث الى مجموعه من التوصيات أهمها ، وضع نظام وتعليمات خاصة تضبط موضوع التعيين والتكليف في الفئات الوظيفيه العليا ضمن شروط وقيود وضوابط قانونية محدده ، إضافة الى تفعيل النصوص القانونية الخاصة بالغاء شرط السلامة الأمنية وضمان تطبيقها في المؤسسات والمرافق الإدارية ، وضع نظام أو لائحة من قبل مجلس الوزراء تحدد طبيعة الوظيفه العامة المسندة للموظف بموجب عقد ويحدد فيها جميع القواعد القانونية التي تحكم موظفي العقود الإدارية . Abstracts This research, which is the subject of the special foundations for the general employee to assume the tasks of the public job, dealt with all the basic provisions and rules that allow the employee to assume the tasks of the public job, starting with the terms of appointment, which were talked about in the first requirement, whether they are conditions specific to the job or conditions specific to the employee himself, in addition to the most important principles Which governs appointment to the public job, and this is all within the item of controls that govern the public job, while the second requirement was talked about the methods of selecting employees and their association with the public job. Means that create the organizational relationship of the employee with management. The research reached a set of recommendations, the most important of which is the development of a system and special instructions that control the issue of appointment and assignment in the higher job categories within specific legal conditions, restrictions and controls, in addition to activating the legal texts for abolishing the security safety condition and ensuring its application in institutions and administrative facilities. Before the Council of Ministers, the nature of the public position assigned to the employee is determined by virtue of a contract, and all legal rules governing administrative contract employees are determined in it.
المجلد13 العدد2
Keywords: التعيين.السلطة.ظيفه. م ; ظف; appointment.Authority .employee